Somatosensory inputs by application of KinesioTaping: effects on spasticity, balance, and gait in chronic spinal cord injury - Tamburella, Federica; Scivoletto, Giorgio; Molinari, Marco (Frontiers in Human Neuroscience, 2014)
Introduction: Leg paralysis, spasticity, reduced interlimb coordination, and impaired balance are the chief limitations to overground ambulation in subjects with incomplete spinal cord injury (SCI). In recent years, the application of KinesioTaping (KT) has been proposed to enhance sensory inputs, decreasing spasticity by proprioception feedback and relieving abnormal muscle tension. Because no studies have examined KT-based techniques in SCI subjects, our goal was to analyze the effects of ankle joint KT on spasticity, balance, and gait. Materials and Methods: A randomized crossover case control design was used to compare the effects of KT and conventional nonelastic silk tape (ST) in 11 chronic SCI subjects, AIS level D, with soleus/gastrocnemius (S/G) muscle spasticity and balance and gait impairments. Treatment: 48 h of treatment with KT or ST was followed by 48 h with the other technique after 1 week. A single Y-strip of Cure© tape (KT) and ST was to the S and G muscles with 0% stretch. Before and 48 h after of application of KT and ST, clinical data on the range of motion (ROM), spasticity, clonus, pain, balance, and gait were collected. Stabilometric platform assessment of center of pressure (COP) movements; bidimensional gait analysis; and recording of electromyographic (EMG) activity of the S, G, and tibialis anterior and extensor hallucis lungus muscles were also performed. Results: Only KT had significant effects on spasticity (p < 0.05), clonus (p < 0.001) and COP movements (p < 0.05), kinematic gait parameters (p < 0.001), and EMG activity (p < 0.001). Comparison between ST and KT improvements pointed out significant differences as concerns ROM (p < 0.001), spasticity (p < 0.001), clonus (p < 0.001), pain (p < 0.001), COP parameters (p < 0.05), and most kinematic gait data (p < 0.05). Discussion: Short-term application of KT reduces spasticity and pain and improves balance and gait in chronic SCI subjects. Although these data are promising, they require confirmation in a larger cohort of patients.